المصطلح الصوتي وتحدياته في العصر الراهن The phonetic term and its challenges in the current era (مجلة إحالات, 2026)
لقد شهد العالم مؤخرا ثورة من المعرفة والمعلومات مع حلول عصر التكنولوجيا، وفي ظل هذا العصر عرفت اللغة العربية عدة مصطلحات توافدت إلينا من الغرب، وبفعل الاختلاف في الترجمة أصبح المصطلح الأجنبي الواحد يقابله عدّة مصطلحات عربيّة، وهذا ينطبق بالذات على المصطلحات الصوتية واللسانية بوجه عام، وقد استهدف هذا على وجه الخصوص العملية التعليمية ، بحيث أصبح الطالب يعاني تشتت في المصطلحات، فكل معلم وطريقته في التدريس وكلٌ والمصطلحات التي يدرس بها، وهذا الإشكال للأسف موجود حتى في المصادر والمراجع التي نستقي منها ما يناسبنا من مصطلحات، ومع ذلك يظل المصطلح الصوتي مصطلحا صوتيا في ظل لغة قوية ومتينة بمرتكزاتها، فالتعبير بالمصطلح القديم والحديث لا يعني بحال انفصال حلقات الزمن بعضها عن بعض، بل هناك تداخل وتشابك في المفاهيم. الكلمات الـمفتاحية: التعدد؛المصطلح الصوتي ؛العصر الراهن ؛التحدي.Abstract : The world has recently attend a revolution of knowledge and information with the advent of the technology age, in this period the Arabic language knew several terms come from the occidentals to us, and due to the difference in translation the foreign term translated into several Arabic terms which is particularly applied on phonetic terms and on linguistic terms in general, this has been especially aimed the didactic process, and impact the student and his application of terms, especially that each teacher have his teaching method and his own terms in teaching, unfortunately we can find this problematic in resources and references from which we took the terms in use, however the phonetic term remains a phonetic term in a strong language with its foundation, then the expression by the old and modern terms does not mean that the tow era was separating in time but there is overlap and texture in concepts.